Subnational Poverty in Mexico and the Social Infrastructure Fund (FAIS) - Ríos, Cesar Gurrola (2024)
Extensive empirical evidence has demonstrated that poverty and social inequality negatively affect society’s general development and economic growth. The Fondo de Aportaciones para la Infraestructura Social (FAIS) (Social Infrastructure Fund) has stood out as one of the main mechanisms of the Mexican government to combat poverty. Faced with the hypothesis of FAIS’s insufficient effectiveness, this study analyzes the impact of the fund’s different components on the poverty levels of Mexico’s states. The study uses a panel data model with biannual observations from 2016 to 2022 from the Mexican government databases. The analysis shows that resources allocated to water, sanitation, and urbanization projects significantly affect the poverty growth rate in Mexican subnational entities. The study results are relevant for economic agents interested in improving the living conditions of the Mexican population through the design, implementation, and monitoring of public policies aimed at combating poverty in Mexico.